Analysis of Marketing Strategies in Increasing Sales at Karimah Dimsum in an Islamic Economic Perspective - Tamima, Aqila; Nawawi, Zuhrinal M. (AMK : Abdi Masyarakat UIKA, 2024)
Islam has a positive attitude towards economic activity. The more Muslims are involved in economic activities, the better if the goals of the process are consistent with Islamic teachings. Becoming an entrepreneur is a solution to the financial problems of Muslims, especially the high poverty rate. The main factors in Micro, Small, and Medium Enterprises (MSMEs) that are of concern are marketing strategy, customer satisfaction, production and distribution, and price changes. This research aims to determine the marketing strategy carried out by one of the strengthening MSMEs in Batu Bara. The research method uses qualitative methods with an approach using qualitative descriptive methods. Data collection techniques using observation, interviews, and documentation to obtain real data in the field of marketing. The analysis techniques used are data reduction, data presentation, and drawing conclusions and verification. The results of this research are that in carrying out the marketing strategy for Dimsum Karimah, which is a pioneer of MSMEs in the Batu Bara area, it uses a marketing mix (Product, Price, Promotion, and Location). The products sold are quality, prices match the quality, promotions with the arrival of the ball, providing testers and social media assistance. And its strategic location. The Islamic marketing strategy is to apply the principle of justice, and the principle of honesty by not comparing the product with other dim sum products, maximum service, and not doing things wrong in setting prices and promotions. In increasing sales of dimsum karimah, namely by maintaining the quality of its products which have been proven to be halal, carrying out promotions assisted by the social media Instagram. It is hoped that the implementation of the marketing strategy can set an example for other MSMEs, not only is margin a priority but good service can make consumers continue to choose Dimsum Karimah as a place to buy snacks in the Batu Bara area.